2021
DOI: 10.1002/eat.23500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress on chewing and food intake in patients with anorexia nervosa

Abstract: Objective The present study investigates the impact of psychosocial stress on chewing and eating behavior in patients with anorexia nervosa (PAN). Method The eating and chewing behavior of PAN were examined in a standardized setting by means of a chewing sensor. These procedures encompassed n = 19 PAN, age, and gender matched to n = 19 healthy controls (HC). Food intake and chewing frequency were assessed in two experimental conditions: rest versus stress (via Trier Social Stress Test). To verify stress induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Chewing is an understudied area of eating disorders, despite the fact that chewing and spitting behaviors are observed frequently in adolescent females [109]. Orosensory stimulation may be reinforcing in some individuals with eating disorders, as evidenced by the fact that social stress increases chewing rates in AN as compared to healthy individuals [110], and by modified sham feeding observations that women with BN sip more liquids [111] and women with AN sip less liquids [112] (independent of swallowing) than healthy individuals. More laboratory studies linking eating behaviors with gastrointestinal interoception are needed.…”
Section: Tasting and Chewingmentioning
confidence: 99%
“…Chewing is an understudied area of eating disorders, despite the fact that chewing and spitting behaviors are observed frequently in adolescent females [109]. Orosensory stimulation may be reinforcing in some individuals with eating disorders, as evidenced by the fact that social stress increases chewing rates in AN as compared to healthy individuals [110], and by modified sham feeding observations that women with BN sip more liquids [111] and women with AN sip less liquids [112] (independent of swallowing) than healthy individuals. More laboratory studies linking eating behaviors with gastrointestinal interoception are needed.…”
Section: Tasting and Chewingmentioning
confidence: 99%
“…Three studies were identified that applied passive sensing to measure characteristics of eating behavior among individuals with EDs (see Table 1). Two studies utilized concealed table weight sensors (Gosnell et al, 2001; Laessle & Schulz, 2009) to measure amount of food consumed, duration and rate of eating, and size of spoonfuls, whereas the third study used an audio sensor to measure chewing rate (Schmalbach, Herhaus, Passler, Schmalbach, et al, 2021). Methodological quality of these studies was moderate (mean quality assessment score = 4.33, range = 3–5 out of 7; all studies were non‐ambulatory).…”
Section: Resultsmentioning
confidence: 99%
“…Because the price of sensors measuring eating behavior can vary widely (i.e., from <$20 for load sensors that can be integrated into tabletops or plates to $5000+ for smart appliances equipped with sensors), researchers should carefully consider sensor capabilities required to answer their research questions. Finally, the three studies that have used sensors to measure eating behaviors have exclusively focused on binge eating disorder (BED; Gosnell et al, 2001; Laessle & Schulz, 2009) and anorexia nervosa (AN; Schmalbach, Herhaus, Passler, Schmalbach, et al, 2021). Additional research should apply these sensors to other diagnostic populations, including bulimia nervosa (BN) and other specified feeding and eating disorder (OSFED) diagnoses.…”
Section: Resultsmentioning
confidence: 99%